Investigations on Receiver sensitivity of 10 Gbps SOA based optical communication system - Singh, Sukhbir; Singh, Kulwinder (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper, investigations are done for performance improvement of optimized SOA preamplifier [13] for 32, 64 channels and various channel spacing. The effects of number of channels and channel spacing are analyzed in terms of receiver sensitivity of the optimized preamplifier based optical receiver.